The exiles : a novel - Kline, Christina Baker, 1964- (William Morrow, an imprint of HarperCollinsPublishers, 2020)
Sent to a Tasmanian penal colony after conceiving her employer's grandchild, a young governess befriends a talented midwife and an orphaned Aboriginal chief's daughter while confronting the harsh realities of British colonialism and oppression in nineteenth-century Australia.